2016
DOI: 10.3390/nu8030127
|View full text |Cite
|
Sign up to set email alerts
|

A Pre and Post Survey to Determine Effectiveness of a Dietitian-Based Nutrition Education Strategy on Fruit and Vegetable Intake and Energy Intake among Adults

Abstract: The purpose of the study was to evaluate the effectiveness of a multicomponent nutrition education program among adults. A pretest—posttest design was used assessing Nutritional Knowledge (NK), BMI, Energy Intake (EI), Physical Activity Level (PAL), Dietary Intake (DI) and attitudes. 353 adults aged 19–55 years (178 control group (CG) and 175 intervention group (IG)) were recruited. IG participants attended nutrition education sessions evaluated through a post-test given at the end of the 12-week program. Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Recently Pem et al [64] also reported a significant increase in fruit intake but no intervention effect for vegetable intake. The differing results among the intervention studies may be explained by the fact that fruit and vegetable intake are influenced by factors like regional differences, education, income, and knowledge, but also fruit and vegetable consumption depends on the sensory appeal, time constraints, familiarity, and availability and accessibility [65]. Gough et al [66] reported a decrease of 1.3 kg in weight and a decrease of 0.5 kg·m −2 in body mass index at 3 months follow up which, however, was not sustained at 12 months’ post intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Pem et al [64] also reported a significant increase in fruit intake but no intervention effect for vegetable intake. The differing results among the intervention studies may be explained by the fact that fruit and vegetable intake are influenced by factors like regional differences, education, income, and knowledge, but also fruit and vegetable consumption depends on the sensory appeal, time constraints, familiarity, and availability and accessibility [65]. Gough et al [66] reported a decrease of 1.3 kg in weight and a decrease of 0.5 kg·m −2 in body mass index at 3 months follow up which, however, was not sustained at 12 months’ post intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in most of these campaigns, improving nutrition knowledge is a target to favour better dietary intakes within the population (3) . In that context, nutrition knowledge is therefore an important indicator to measure the impact of these public health interventions (7)(8)(9) .…”
mentioning
confidence: 99%
“…This may be due to a greater desire to lose weight among women and older adults being more time rich than younger adults. In addition, individuals with greater motivation to be healthy and to participate in nutrition interventions may be more knowledgeable about the benefits of healthy eating (35) . Similarly, of the 5662 individuals who expressed an interest in participating in the Food4Me Study, 65 % were women (9) .…”
Section: Discussionmentioning
confidence: 99%